CYBB/NOX2 in conventional DCs controls T cell encephalitogenicity during neuroinflammation - Keller, Christian W. (Autophagy, 2020)
Whereas central nervous system (CNS) homeostasis is highly dependent on tissue surveillance by immune cells, dysregulated entry of leukocytes during autoimmune neuroinflammation causes severe immunopathology and neurological deficits. To invade the CNS parenchyma, encephalitogenic T helper (T(H)) cells must encounter their cognate antigen(s) presented by local major histocompatibility complex (MHC) class II-expressing antigen-presenting cells (APCs). The precise mechanisms by which CNS-associated APCs facilitate autoimmune T cell reactivation remain largely unknown. We previously showed that mice with conditional deletion of the gene encoding the essential autophagy protein ATG5 in dendritic cells (DCs) are resistant to EAE development. Here, we report that the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2, also known as CYBB/NOX2, in conventional DCs (cDCs) regulates endocytosed MOG (myelin oligodendrocyte protein) antigen processing and supports MOG-antigen presentation to CD4(+) T cells through LC3-associated phagocytosis (LAP). Genetic ablation of Cybb in cDCs is sufficient to restrain encephalitogenic T(H) cell recruitment into the CNS and to ameliorate clinical disease development upon the adoptive transfer of MOG-specific CD4(+) T cells. These data indicate that CYBB-regulated MOG-antigen processing and LAP in cDCs licenses encephalitogenic T(H) cells to initiate and sustain autoimmune neuroinflammation. Abbreviations: Ag: antigen; APC: antigen-presenting cell; AT: adoptive transfer; ATG/Atg: autophagy-related; BAMs: border-associated macrophages; BMDC: bone marrow-derived DC; CD: cluster of differentiation; CNS: central nervous system; CSF2/GM-CSF: colony stimulating factor 2 (granulocyte-macrophage); CYBB/NOX2/gp91(phox): cytochrome b-245, beta polypeptide; DC: dendritic cell; EAE: experimental autoimmune encephalomyelitis; fl: floxed; FOXP3: forkhead box P3; GFP: green fluorescent protein; H2-Ab: histocompatibility 2, class II antigen A, beta 1; IFN: interferon; IL: interleukin; ITGAX/CD11c: integrin subunit alpha X; LAP: LC3-associated phagocytosis; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MFI: median fluorescence intensity; MG: microglia; MHCII: major histocompatibility complex class II; MOG: myelin oligodendrocyte glycoprotein; MS: multiple sclerosis; NADPH: nicotinamide adenine dinucleotide phosphate; ODC: oligodendroglial cell; OVA: ovalbumin; pDC: plasmacytoid DC; Ptd-L-Ser: phosphatidylserine; PTPRC: protein tyrosine phosphatase, receptor type, C; ROS: reactive oxygen species; SLE: systemic lupus erythematosus; T(H) cells: T helper cells; TLR: toll-like receptor; ZBTB46: zinc finger and BTB domain containing 46